Sistem Pakar Diagnosa Hama Penyakit Tanaman Tomat Menggunakan Metode Forward Chaining - Alberta mbagho; Meliana O. Meo; Gregorius Rinduh Iriane (Infact: International Journal of Computers, 2023)
The tomato (Solanum lyco persicum) is a plant from the solanceae family, native to Central and South America, from Mexico and Peru. Tomatoes have a short life cycle and height from I to 3 meters. Currently, farmers often ignore pests and diseases of tomatoes due to lack of knowledge. They also assessed that it finally happened at the time of planting, experts on pests and diseases of tomatoes were eliminated, there was a lack of socialization from agricultural officials about pests and diseases in tomatoes, but they did not know how to control them and to eliminate diseases quickly or decrease productivity. This study uses the Forward Chaining method, which is a description that starts from known facts and then is matched with IF and IF-THEN rules. Pests and diseases with a high prevalence in tomatoes are pests. Some pests are: fruit caterpillars, earthworms, green aphids, white flies, fruit flies (bractrotera) and further diseases namely: Fusarium wilt, leaf spot disease, bacterial spots, fruit rot. This expert system application provides information on tomato diseases and disease diagnosis, including control solutions that can be used to reduce the risk of damage to tomato plants. This study aims to build an expert system application that can diagnose tomato plant pests and diseases using the forward chaining method. This application is expected to help the community in diagnosing the types of tomato plant pests. The implementation of the application of an expert system for pests and diseases of tomato plants is expected to provide easy access for users and the wider community, through the use of web-based media.